Batch Nanofabrication of Suspended Single 1D Nanoheaters for Ultralow‐Power Metal Oxide Semiconductor‐Based Gas Sensors. Issue 48 (30th September 2022) - Kim, Taejung; Cho, Wootaek; Kim, Beomsang; Yeom, Junyeong; Kwon, Yeong Min; Baik, Jeong Min; Kim, Jae Joon; Shin, Heungjoo
Abstract: The demand for power‐efficient micro‐and nanodevices is increasing rapidly. In this regard, electrothermal nanowire‐based heaters are promising solutions for the ultralow‐power devices required in IoT applications. Herein, a method is demonstrated for producing a 1D nanoheater by selectively coating a suspended pyrolyzed carbon nanowire backbone with a thin Au resistive heater layer and utilizing it in a portable gas sensor system. This sophisticated nanostructure is developed without complex nanofabrication and nanoscale alignment processes, owing to the suspended architecture and built‐in shadow mask. The suspended carbon nanowires, which are batch‐fabricated using carbon‐microelectromechanical systems technology, maintain their structural and functional integrity in subsequent nanopatterning processes because of their excellent mechanical robustness. The developed nanoheater is used in gas sensors via user‐designable localization of the metal oxide semiconductor nanomaterials onto the central region of the nanoheater at the desired temperature. This allows the sensing site to be uniformly heated, enabling reliable and sensitive gas detection. The 1D nanoheater embedded gas sensor can be heated immediately to 250 °C at a remarkably low power of 1.6 mW, surpassing the performance of state‐of‐the‐art microheater‐based gas sensors. The presented technology offers facile 1D nanoheater production and promising pathways for applications in various electrothermal devices. Abstract : A suspended 1D nanoheater capable of ultrarapid heating to 250 °C at an ultralow‐power of 1.6 mW is demonstrated; its production is facilitated at the water level owing to the suspended 1D architecture and built‐in shadow mask. The nanoheater is implemented as a gas sensor by the regioselective localization of metal oxide semiconductor nanomaterials, enabling reliable and sensitive gas detection.